THE EXPLORING PPRST STRATEGIES FOR READING INSTRUCTIONAL - Nurbianta -; Amrizal - (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2017)
Reading as one of the macro skills of English is an important part in English Language Teaching. It should be mastered by guiding intensively to get a good achievement, so, it can bring positive impact to understand the writer ideas in the text clearly. That is why, practicing the-PPRST (Personal and study assessment, Point of study progression, Re-Framing Learning, Study session, Testing session) strategies can be the way in training the students to get an achievement. This study sought to answer the questions; (1) What strategies can be implemented to enhance the reading comprehension of the 4th-semester students of STIT Muhammadiyah Tanjung Redeb?, and (2) What is the performance of the control and experimental classes in the pre-test and post-test?. The data were collected in Sekolah Tinggi Ilmu Tarbiyah (STIT) Muhammadiyah, Tanjung Redeb City, Berau Regency of East Kalimantan. Participants were 30 students at the 4th semester of STIT Muhammadiyah Tanjung Redeb. The design of research is experimental and statistical tools for analyzing the data use T-Test. Finding are: PPRST is being the suit strategies to help students in increasing the high score in reading test., the Pre-test result of the control group is 49.83 and experimental group is 52.66. After the treatment, the post-test was administered and the same analysis with the pre-test was done with the results of Post-test in control group is 59.00 and experimental group is 70.00.